Clinical and laboratory predictors of coronary slow flow in coronary angiography. (January 2017) - Ghaffari, Samad; Tajlil, Arezou; Aslanabadi, Naser; Separham, Ahmad; Sohrabi, Bahram; Saeidi, Gholamreza; Pourafkari, Leili
Background: The coronary slow-flow phenomenon (CSFP) is a multifactorial angiographic finding with no established pathogenesis. Objective: To investigate the role of clinical profile and laboratory findings in patients with CSFP. Methods: We prospectively recruited 69 patients with angiographically diagnosed CSFP and compared them with 88 patients with normal coronary flow. Demographic information, comorbidities and laboratory analysis, including complete blood count with differential, lipid profile and serum biochemical analysis, were documented and compared in univariate and multivariate analyses. Results: Patients with CSFP were more likely to be male and active smokers. Total cholesterol, triglyceride, hemoglobin and hematocrit, platelet count, mean platelet volume, platelet distribution width and red cell distribution width (RDW) were all higher in patients with CSFP. In multivariate regression analysis, including smoking, total cholesterol, hematocrit, fasting blood glucose and red cell distribution width, except fasting blood glucose, all variables were independently associated with CSFP. Receiver operating characteristic curve analysis revealed a cut-off point of 13.05% for RDW with a sensitivity of 74.6% and a specificity of 77.3% (p<0.001, AUC = 0.802) A cut-off value of 11.35% for PDW had a 89.9% sensitivity and 98.9% specificity for the prediction of CSFP (p<0.001, AUC = 0.970) Conclusion: The changes of circulating blood cell components in patients with CSFP may be indicative of underlying inflammation and endothelial dysfunction that should be investigated in experimental studies.